How Research Can Assist Policy : The Case of Economic Reforms in Uganda - Mackinnon, John; Reinikka, Ritva (World Bank, 2013)
Research has had a powerful impact on policy in Uganda, affecting the climate of opinion, improving the quality of the policy debate, and helping focus public policy and intervention on poverty reduction. Uganda s successful use of knowledge and research to help set public policy priorities demonstrates that even a poor post conflict country can, in a relatively short period of time, create an effective information base and feedback mechanisms for decision making.